Influence of joint line remnant on crack paths under static and fatigue loadings in friction stir welded Al-Mg-Sc alloy (Fracture and Structural Integrity, 2015)
The influence of the joint line remnant (JLR) on tensile and fatigue fracture behaviour has been investigated in a friction stir welded Al-Mg-Sc alloy. JLR is one of the microstructural features formed in friction stir welds depending on welding conditions and alloy systems. It is attributed to initial oxide layer on butting surfaces to be welded. In this study, two different tool travel speeds were used. JLR was formed in both welds but its spatial distribution was different depending on the tool travel speeds. Under the tensile test, the weld with the higher heat input fractured partially along JLR, since strong microstructural inhomogeneity existed in the vicinity of JLR in this weld and JLR had weak bonding. Resultantly, the mechanical properties of this weld were deteriorated compared with the other weld. Fatigue crack initiation was not affected by the existence of JLR in all welds. But the crack propagated preferentially along JLR in the weld of the higher heat input, when it initiated on the retreating side. Consequently, such crack propagation behaviour along JLR could bring about shorter fatigue lives in larger components in which crack growth phase is dominant.
Keywords: Friction Stir Weld (FSW); Aluminium alloy; Fatigue